Cape Verde : Poverty Reduction and Growth Strategy Paper - II. (IMF Staff Country Reports; Country Report, 2008)
This paper focuses on Poverty Reduction and Growth Strategy Paper-II (GPRSP II) for Cape Verde. The GPRSP II is formulated with reference to five major strategic aims concerning good governance, human capital, competitiveness, infrastructure building, and social cohesion. In identifying and pursuing these aims, the country seeks to improve its performance with respect to the established objectives and targets. The central objective of poverty reduction rests primarily upon structural policies linked to the promotion of inclusive economic growth, complemented by redistributive policies that are socially compensatory and focused on groups with high vulnerability.